Suturing fragmented landscapes: Mosaic hybrid zones in plants may facilitate ecosystem resiliency - Rob Massatti; Trevor M. Faske; Ivana M. Barnes; Elizabeth A. Leger; Thomas L. Parchman; Bryce A. Richardson; L. Lacey Knowles (Proceedings of the National Academy of Sciences, 2025)
Many widespread plant taxa of western North America have diversified into phenotypically and genetically divergent lineages due to complex biogeographic histories across heterogeneous landscapes. Mosaic hybrid zones can form when geographically co-occurring, yet environmentally distinct, lineages cross-pollinate and form hybrids that occupy unique environmental niches absent of a geographic cline. This expands the total environmental space across which parental and hybrid individuals grow, resulting in larger, less fragmented geographic distributions. Here, we highlight hybridization mosaics across three study systems containing taxa critical to widespread plant communities in western North America: Ericameria nauseosa , Artemisia tridentata , and Sphaeralcea fendleri . The systems contain diverged taxa that co-occur across the landscape and hybridize readily. Hybridization among taxa has facilitated niche expansion into intermediate environments consistent with unique combinations of adaptive genetic variation, creating more continuity within each study system—study systems occupy ~820 to 270,000 km 2 more geographic area by virtue of hybridization. Furthermore, hybrids are predicted to play important roles in future climates, as they may occupy 8 to 475% larger distributions compared to present. Convergent patterns signal mosaic hybridization as an underappreciated mechanism with broad ecological and evolutionary ramifications. Leveraging mosaic hybridization may assist the creation of restoration management plans that aim to mitigate the deleterious effects of habitat fragmentation on ecosystems in the context of climate change.